2009
DOI: 10.1186/1471-2148-9-171
|View full text |Cite
|
Sign up to set email alerts
|

A species delimitation approach in the Trochulus sericeus/hispiduscomplex reveals two cryptic species within a sharp contact zone

Abstract: Background: Mitochondrial DNA sequencing increasingly results in the recognition of genetically divergent, but morphologically cryptic lineages. Species delimitation approaches that rely on multiple lines of evidence in areas of co-occurrence are particularly powerful to infer their specific status. We investigated the species boundaries of two cryptic lineages of the land snail genus Trochulus in a contact zone, using mitochondrial and nuclear DNA marker as well as shell morphometrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…The non-monophyly of Partula taeniata on both COI and 28S trees is a good example: this result may indicate that species delineations are in this case not accurately assessed. Once again, FTA cards are particularly useful from a conservation perspective: the lack of knowledge on the status of the populations (endangered or not), often severely impacted by habitat destruction and introduction of invasive species and in which the taxonomic delimitation of species are often unclear (Depraz et al 2009;Uit de Weerd 2008), would push the collector to apply the precautionary principle and to not destroy the specimens. In the particular case of species delimitation and description, the FTA card method could be also very interesting.…”
Section: Discussionmentioning
confidence: 99%
“…The non-monophyly of Partula taeniata on both COI and 28S trees is a good example: this result may indicate that species delineations are in this case not accurately assessed. Once again, FTA cards are particularly useful from a conservation perspective: the lack of knowledge on the status of the populations (endangered or not), often severely impacted by habitat destruction and introduction of invasive species and in which the taxonomic delimitation of species are often unclear (Depraz et al 2009;Uit de Weerd 2008), would push the collector to apply the precautionary principle and to not destroy the specimens. In the particular case of species delimitation and description, the FTA card method could be also very interesting.…”
Section: Discussionmentioning
confidence: 99%
“…This genus has frequently been the focus of taxonomic questions, which have been addressed using morphological (Focart, 1965; Gittenberger, Backhuys & Ripken, 1970; Schileyko, 1978; Falkner, 1995; Falkner, Ripken & Falkner, 2002; Proćków, 2009; Duda et al ., 2011) and genetic data (Pfenninger et al ., 2005; Dépraz, Hausser & Pfenninger, 2009; Kruckenhauser et al ., 2014). The species with the widest distribution within the genus is T. hispidus (Linnaeus, 1758).…”
Section: Introductionmentioning
confidence: 99%
“…Proćków, 2009). Based on molecular analyses, some authors have suggested splitting T. hispidus into several cryptic species (Pfenninger et al ., 2005; Dépraz et al ., 2009). In a survey of Trochulus species from Germany, Switzerland and France, Pfenninger et al (2005) found several highly distinct mt clades which could, however, not be classified unambiguously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since morphological taxonomy relies on visible traits, it has been suggested that cryptic species may be more frequent when non-visual cues dominate intra-species interactions and hence selection for morphological traits is limited [8]. The soil is one such case, and analyses for springtails [9], oribatids [10] and molluscs [11,12] have all revealed a high degree of crypsis. Earthworms have high potential for local population isolation, and many named earthworm species are probably species complexes [13].…”
Section: Introductionmentioning
confidence: 99%